Development of a queueing model for communication congestion control in the production industry - Kareem, Buliaminu; Olusegun Gbolagade, Adeyemi (Journal of Production Engineering, 2023)
A M/M/1 queueing model was developed to control communication congestion in the production industry. The arrival rate of the customers and the link capacity of the system were used as the input parameters to determine congestion state of the system and the mean service rate at which congestion can be avoided. Server utilisation, delay time, probability of blocking and through put of the system were used as the performance measure of the model to determine the optimal point at which congestion can be avoided in a manufacturing system. The model is based on first-come-first-serve service discipline. A computer program using visual basic was developed for quick evaluation and to determine the optimal point and the congestion state of the networks after the series of iteration.